A note on Old Prussian epigram - Kortlandt, Frederik (Baltistica, 2018)
The Old Prussian epigram was probably written by a Bavarian scribe to whom the text was dictated by a native speaker of Prussian.
Keywords: Old Prussian; Basel epigram